Keadilan Anak Dan Hak-Hak Pelaku Kejahatan Remaja - Maria Ferba Editya; Jimmy Prisma Sinuhaji (Journal Recht (JR), 2025)
The focus of this research is to understand the types of legal protection provided by the authorities to children who commit criminal acts. The type of research used is library research. Based on the research results, it was determined that at each stage of the juvenile delinquency process, there are types of support offered to juvenile delinquents. Starting from the point of arrest, the point of detention, the point of investigation, trial and after trial, including the training period. Another form of support is efforts to resolve criminal cases outside of court, meaning that children's cases are always resolved through various means, and this must be done in all areas of juvenile delinquency. The aim of legal protection for child perpetrators is to respect the human rights of perpetrators so that their mental health is not disturbed, their legal rights are respected, and their actions are avoided continuously and unjustly.